Analysis Of Rendang IKM Center Development In Payakumbuh - Sufiawan, Nur Ari (Inovbiz: Jurnal Inovasi Bisnis, 2023)
This study aims to analyze the strategy of developing IKM rendang to penetrate the Modern and International markets. This type of qualitative research. The data used are primary data obtained from direct interviews with respondents using a questionnaire in IKM Rendang Padang Kaduduak, North Payakumbuh Regency. Data analysis in this study uses several approaches, namely IFAS and EFAS Analysis, Alternative Strategies, and Priority Strategies. The results of the study explain that the SPACE matrix where the Cartesian diagram is located is in quadrant I where the organization/business is in prime and stable condition, so it is very possible to continue to grow. Based on this, it can be concluded that it can provide strength to take advantage of existing opportunities and support aggressive growth policies.